PENGARUH BEBAN LALU LINTAS TERHADAP KERUSAKAN LENTUR DI JALAN TOL BERDASARKAN METODE PAVEMENT CONDITION INDEX (Studi Kasus Ruas Lingkar Luar Jakarta (JORR) W2 Utara Jalur A dan B): INFLUENCE OF TRAFFIC LOAD ON FLEXIBLE DAMAGE ON TOLL ROADS BASED ON PAVEMENT CONDITION INDEX METHOD Case Study: the North Jakarta Outer Ring Road (JORR) W2 Lines A and B - Bayu Wiedjayantoro; A R Indra Tjahjani (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2021)
Jorr toll road function as a network of roads that serves to break down the traffic that currently accumulates in the city of Jakarta, so that this toll road will facilitate the flow of traffic from bogor / Jagorawi towards Tangerang / Merak, and vice versa. With the perfect JORR, it will be one of the alternatives to Soekarno-Hatta International Airport. Jakarta W2 Utara Outer Ring Road is often crowded with traffic during certain hours. So in the field there are many locations of pavement damage where as large in the lane of heavy-laden and overloaded vehicles. Differences in traffic load can cause different levels of road damage between lanes. The extent of road damage can be evaluated by using the PCI method. The purpose of this study is to evaluate the effect of traffic load on flexible damage based on PCI method with the level and type of damage in each lane can be identified.